Two years in California. - Cone, Mary. (Chicago, S.C. Griggs and company, 1876)
A resident of Marietta, Ohio, Mary Cone spent two years in California in the 1870s. Two years in California (1876) is more a guide than a first-person narrative of her experiences in the West. She treats the state's history, climate, agriculture, and geography before turning to its regions: Southern California (San Diego, Los Angeles, Santa Barbara), the Sacramento and San Joaqun̕ Valleys (with chapters on individual Sacramento ranches), Northern California's redwoods and Mount Shasta and the same region's other tourist attractions (San Francisco, Mount St. Helena). Separate chapters discuss the Chinese in California and the author's visit to Yosemite.
Also available in digital form on the Library of Congress Web site.
Also available in digital form on the Internet Archive Web site.
Keywords: California -- Description and travel; Ethnic groups -- California; Women -- California; Urbanization -- California; Real estate development -- California; Agriculture -- California